Вік кримінальної відповідальності як проблема юридичної науки і практики - Кузьменко, Олександр Васильович (НТУ "ХПІ", 2016)
У статті аналізується сучасний стан вивчення проблеми залежності між віковими особливостями дитини та її здатністю нести кримінальну відповідальність. Здійснюється огляд відповідних теоретичних та експериментальних досліджень вітчизняних і зарубіжних вчених в галузі правознавства, психології, педагогіки. Використовуються матеріали судової практики і дані правової статистики. Наводяться доводи на користь доцільності зниження в Україні початкового віку кримінальної відповідальності.

The article analyzes the current state of scientific study of the relationship between age-related characteristics of the child and its ability to bear criminal liability. The author analyzes the relevant theoretical and experimental studies of domestic and foreign scientists in the fields of psychology, pedagogy, law. The author uses the materials of judicial practice and the data of legal statistics. The researcher proves the need to reduce the starting age of criminal responsibility in Ukraine. The author supports periodization of children's development, which has legal significance and is offered in the modern legal literature. Children under 11 years are outside the scope of criminal punishment and cannot be prosecuted. Children between 11-14 years should be brought to criminal responsibility only for the comprehensive list of crimes. Before that, they must undergo review for compliance with the actual level of their development and chronological age.
Age of criminal responsibility as a problem of legal science and practice
Keywords: кримінальне законодавство; підліткова злочинність; вікова осудність; суб’єкт злочину; правова статистиа; age of criminal responsibility; age-related responsibility; subject of crime; juvenile criminality; ocialization